2014
DOI: 10.1002/pro.2425
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the SENP6 Loop1 structure in complex with SUMO2

Abstract: The SENP proteases regulate the SUMO conjugates in the cell by cleaving SUMO from target proteins. SENP6 and SENP7 are the most divergent members of the SENP/ULP protease family in humans by the presence of insertions in their catalytic domains. Loop1 insertion is determinant for the SUMO2/3 activity and specificity on SENP6 and SENP7. To gain structural insights into the role of Loop1, we have designed a chimeric SENP2 with the insertion of Loop1 into its sequence. The structure of SENP2-Loop1 in complex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…12,43 This feature is thought to contribute to its specificity for SUMO chains. 44 We found that SENP7 counteracted c-Myc SUMOylation (Fig. 4b).…”
Section: Discussionmentioning
confidence: 71%
“…12,43 This feature is thought to contribute to its specificity for SUMO chains. 44 We found that SENP7 counteracted c-Myc SUMOylation (Fig. 4b).…”
Section: Discussionmentioning
confidence: 71%
“…Here the expectation for stronger allosteric effects is specifically supported by the observation that a pre-bound SUMO2, but not SUMO1, β-grasp domain enhanced the SENP2 catalytic activity on a peptide substrate ( Mikolajczyk et al, 2007 ). A similar causal link between strengthened exosite interactions and strengthened allosteric effects may be at play for a SENP2 mutant that was designed by grafting an insertion in the β1-β2 hairpin from SENP6 ( Alegre and Reverter, 2014 ). The insertion extended the exosite lower interface and increased the proteolytic activity of SENP2 for some SUMO2 conjugates.…”
Section: Discussionmentioning
confidence: 92%
“…Structural studies have shown that SENP catalytic domains only undergo localized conformational rearrangements upon binding SUMOs (as precursors, processed products, or SUMO conjugates), and that SENP-SUMO interactions are largely similar during precursor processing and deSUMOylation ( Reverter and Lima, 2004 , 2006 ; Shen et al, 2006a , 2006b ; Xu et al, 2006 ; Alegre and Reverter, 2014 ). In SENP1, the catalytic triad comprises residues His533, Asp550, and Cys603 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of a chimeric SENP2 fusion harboring the Loop-1 segment from SENP6 bound to SUMO2 revealed that Loop-1, an eight-residue element, extends the binding interface between the protease and SUMO2. A negative patch of amino acids unique to SUMO2 (Asn68, Asp71 and Glu77) directly contacts the SENP6 Loop-1 ( Figure 6E ) 120 . These residues are substituted to Ala, His and Gly in SUMO1, which implicates both the Loop-1 insertion in SENP6/7 and the negative patch of SUMO2 as key determinants in SUMO isoform specificity.…”
Section: Insertions In Catalytic Domains Contribute To Substrate Specmentioning
confidence: 99%